HIV infection in Eastern and Southern Africa: Highest burden, largest challenges, greatest potential - Parker, E; Judge, MA; Macete, E; Nhampossa, T; Dorward, J; Langa, DC; De Schacht, C; Couto, A; Vaz, P; Vitoria, M; Molfino, L; Idowu, RT; et al. (AOSIS, 2021)
Background: The burden of HIV is especially concerning for Eastern and Southern Africa (ESA), as despite expansion of test-and-treat programmes, this region continues to experience significant challenges resulting from high rates of morbidity, mortality and new infections. Hard-won lessons from programmes on the ground in ESA should be shared.